Strega Nona's magic lessons - DePaola, Tomie, 1934- (San Diego, CA : Harcourt, 1982)
Big Anthony disguises himself as a girl in order to take magic lessons from Strega Nona.
"Voyager books.".
Booklist.
Child Study Children's Book Committee.
School Library Journal.
2.8
3.8.
Keywords: Magic -- Juvenile fiction; Magic -- Fiction; Magic -- Fiction